A corrosion-resistant PE cable and its preparation process
By using PVC outer layer, PE inner layer and wire core structure in the cable, and using modified montmorillonite, modified expanded vermiculite and other materials to enhance the performance of the PE inner layer, the cable is easily corroded in harsh environments. and the problem of breaking, achieving high corrosion resistance and toughness of cable products.
Patent Information
- Application Number
- CN202410886480.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-07-03
AI Technical Summary
Existing cables are prone to corrosion, breakage and aging in harsh environments, making it difficult to ensure performance and safety.
Corrosion-resistant PE cable consisting of PVC outer layer, PE inner layer and wire core, a gap is provided between the PE inner layer and the PVC outer layer to provide thermal expansion and contraction space and heat dissipation effect, and modified montmorillonite , modified expanded vermiculite, ethylene acrylic acid and glass fiber and other materials enhance the corrosion resistance and toughness of the inner layer of PE.
It effectively improves the corrosion resistance and toughness of the cable, can maintain stable performance in different environments, and reduces the risk of safety accidents.
Smart Images

Figure CN118866442B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cables, and in particular, relates to a corrosion-resistant PE cable and a preparation process thereof. Background Art
[0002] With the rapid development of science and technology, cables, as an important part of infrastructure such as electricity and communications, have increasingly higher requirements for performance and quality. Especially in some harsh environments, such as chemical, petroleum, and marine fields, cables face multiple threats such as corrosion, breakage, and aging. Although traditional cable materials can meet basic usage needs to a certain extent, their performance is often difficult to guarantee when facing a complex and changeable external environment. Especially in some highly corrosive environments, the outer sheath of the cable is easily corroded, resulting in the exposure of the internal wiring, which can cause safety accidents. In addition, the toughness of traditional cables is insufficient, and they are also prone to breakage when impacted by external forces, which seriously affects their service life and safety. Therefore, it is of great practical significance to provide a corrosion-resistant, high-toughness PE cable that can maintain stable performance in different environments. Summary of the invention
[0003] The purpose of the present invention is to provide a corrosion-resistant PE cable and a preparation process thereof, which solves the problem of poor corrosion resistance and toughness of the cable in the prior art.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A corrosion-resistant PE cable, the cable comprising a PVC outer layer, a PE inner layer and a wire core;
[0006] The PE inner layer is coated on the outer peripheral side of the core, and the PVC outer layer is coated on the outer peripheral side of the PE inner layer. A gap is provided between the PVC outer layer and the PE inner layer, and the PVC outer layer and the PE inner layer are separable. The gap can effectively provide space for thermal expansion and contraction of the corrosion-resistant PE cable when in use. Secondly, the gap is conducive to the heat dissipation of the core;
[0007] The PE inner layer and the PVC outer layer are both formed by mixing and extruding the PE inner layer raw material and the PVC outer layer raw material;
[0008] The PVC outer layer raw material includes PVC resin.
[0009] As a preferred technical solution of the present invention, the PE inner layer raw material specifically includes the following raw materials in parts by weight:
[0010]
[0011] As a preferred technical solution of the present invention, the polyethylene includes HDPE.
[0012] As a preferred technical solution of the present invention, the preparation method of the modified montmorillonite is:
[0013] The montmorillonite and deionized water are stirred evenly under controlled temperature, the pH value of the solution is adjusted after the stirring is completed, and the stirring is continued. After the stirring is completed, hexadecyltrimethylammonium chloride is added, stirred evenly and the pH value of the solution is adjusted, and the stirring is continued. After the stirring is completed, the temperature is lowered, suction filtered, washed, temperature-controlled dried, ground, and sieved to obtain modified montmorillonite.
[0014] Furthermore, the mass ratio of the montmorillonite, deionized water and hexadecyltrimethylammonium chloride is 1:25-28:0.4-0.5.
[0015] Furthermore, the temperature for temperature-controlled stirring is 75-80°C; the pH of the solution is adjusted by using 0.1 mol / L sodium hydroxide solution to adjust the pH of the solution to 7.0-7.2; the time for continued stirring is 20-30 minutes; the time for re-stirring is 1.5-2 hours; the cooling is cooling to 23-25°C; the washing is washing with deionized water 2-3 times; the temperature of temperature-controlled drying is 75-80°C; and the screening is through a 400-mesh sieve.
[0016] As a preferred technical solution of the present invention, the preparation method of the modified expanded vermiculite is:
[0017] The expanded vermiculite and KH550 solution are mixed evenly and stirred at a controlled temperature. After stirring, the mixture is cooled and allowed to stand, filtered, washed, dried at a controlled temperature, ground, and sieved to obtain modified expanded vermiculite.
[0018] Furthermore, the mass ratio of the expanded vermiculite to the KH550 solution is 1:0.05-0.07.
[0019] Furthermore, the KH550 solution is a KH550 ethanol solution with a mass fraction of 20%.
[0020] Furthermore, the temperature of the temperature-controlled stirring is 55-60°C, and the time is 1-1.5h; the cooling and standing is cooling to room temperature and standing for 8-10h; the washing is washing with deionized water 2-3 times; the temperature of the temperature-controlled drying is 100-105°C; and the screening is through a 500-mesh sieve.
[0021] A method for preparing a corrosion-resistant PE cable, the method specifically comprising the following steps:
[0022] S1, drying the ethylene-sodium methacrylate copolymer under vacuum at controlled temperature to obtain the dried ethylene-sodium methacrylate copolymer for standby use;
[0023] S2. Evenly mix polyethylene, modified montmorillonite, modified expanded vermiculite, ethylene acrylic acid, ethylene-octene copolymer, glass fiber and dried ethylene-sodium methacrylate copolymer and place them in a twin-screw extruder for speed and temperature controlled extrusion granulation to obtain PE inner layer pellets, extrude the obtained PE inner layer pellets into shapes, coat them on the outer circumference of the wire core, cool and solidify to obtain a semi-finished cable, extrude PVC resin into shapes, coat them on the outer circumference of the semi-finished cable, cool and solidify to obtain a corrosion-resistant PE cable finished product.
[0024] As a preferred technical solution of the present invention, the temperature of the temperature-controlled vacuum drying in step S1 is 55-60°C and the time is 22-24h.
[0025] As a preferred technical solution of the present invention, the speed of the speed and temperature control in step S2 is 300-350r / min, and the temperature is 180-200°C.
[0026] As a preferred technical solution of the present invention, the extrusion molding conditions in step S2 are: the feeding section temperature is 170-180°C, the compression section temperature is 200-210°C, the plasticizing section temperature is 210-220°C, the homogenizing section temperature is 200-210°C, the mold temperature is 190-200°C, and the cooling water temperature is 15-20°C.
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention adds modified montmorillonite with a high aspect ratio and modified expanded vermiculite with a layered structure. The surface modification of the montmorillonite and the expanded vermiculite effectively increases the compatibility of the expanded vermiculite with the HDPE matrix and reduces the surface energy of the montmorillonite. On this basis, ethylene acrylic acid is also added to interact with the HDPE matrix through the vinyl segments on its molecular chain, further promoting the compatibility of the modified montmorillonite and the modified expanded vermiculite with the HDPE matrix and forming a new interface layer. The stone increases the tortuous path of foreign molecules passing through the material; in addition, the ethylene acrylic acid molecular chain also has carboxyl groups, which can effectively form carboxylic acid metal ion bonds with the ions on the surface of the modified montmorillonite, so that the modified montmorillonite is evenly dispersed in the HDPE, reducing the free volume of the matrix, and further strengthening the path of foreign molecules passing through the material; the PE inner layer pellets thus obtained are used in the preparation of cables, which effectively hinders the diffusion of foreign bodies in the finished cable products, improves the gas-liquid barrier properties of the cables, and increases the corrosion resistance of the finished cable products.
[0029] (2) The present invention adds ethylene-octene copolymer with excellent elastomeric properties to disperse stress, and adds glass fiber with excellent elastic modulus and high tensile strength to absorb most of the impact energy in the material, which to a certain extent assists the ethylene-octene copolymer in improving the toughness of the PE inner layer pellets; at the same time, the present invention also uses ethylene-sodium methacrylate copolymer as a compatibilizer to enhance the interface compatibility between the ethylene-octene copolymer and the glass fiber and HDPE. The PE inner layer pellets thus obtained are used in the preparation of cables, which can make the prepared cables have excellent toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0031] Figure 1 It is a cross-sectional view of the corrosion-resistant PE cable in this application.
[0032] Explanation of the reference numerals: 1, PVC outer layer; 2, gap; 3, PE inner layer; 4, wire core. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The model of the PVC resin used in the embodiment of the present invention is SG-5; the model of montmorillonite is XA-P57; the model of ethylene acrylic acid is EAA-3340; the model of ethylene-octene copolymer is 8180; the model of glass fiber is FR50; the model of ethylene-sodium methacrylate copolymer is Surlyn 8920; no further details will be given later.
[0035] Example 1
[0036] Prepare modified montmorillonite, the preparation method of the modified montmorillonite is:
[0037] The montmorillonite and deionized water were stirred at 75°C, and after stirring, the pH value of the solution was adjusted to 7.1 with 0.1 mol / L sodium hydroxide solution, and the stirring was continued for 30 minutes. After stirring, hexadecyltrimethylammonium chloride was added and stirred evenly, and the pH value of the solution was adjusted to 7.0 with 0.1 mol / L sodium hydroxide solution, and the stirring was continued for 1.5 hours. After stirring, the temperature was lowered to 25°C, filtered, washed twice with deionized water, dried at 75°C, ground, and passed through a 400-mesh sieve to obtain modified montmorillonite.
[0038] The mass ratio of the montmorillonite, deionized water and hexadecyltrimethylammonium chloride is 1:25:0.45.
[0039] Example 2
[0040] Prepare modified montmorillonite, the preparation method of the modified montmorillonite is:
[0041] The montmorillonite and deionized water were stirred at 80°C, and after stirring, the pH value of the solution was adjusted to 7.0 with 0.1 mol / L sodium hydroxide solution, and the stirring was continued for 25 minutes. After stirring, hexadecyltrimethylammonium chloride was added and stirred evenly, and the pH value of the solution was adjusted to 7.2 with 0.1 mol / L sodium hydroxide solution, and the stirring was continued for 2 hours. After stirring, the temperature was lowered to 24°C, filtered, washed with deionized water for 3 times, dried at 78°C, ground, and passed through a 400-mesh sieve to obtain modified montmorillonite.
[0042] The mass ratio of the montmorillonite, deionized water and hexadecyltrimethylammonium chloride is 1:26.5:0.5.
[0043] Example 3
[0044] Prepare modified montmorillonite, the preparation method of the modified montmorillonite is:
[0045] The montmorillonite and deionized water were stirred at 78°C, and after stirring, the pH value of the solution was adjusted to 7.2 with 0.1 mol / L sodium hydroxide solution, and the stirring was continued for 20 minutes. After stirring, hexadecyltrimethylammonium chloride was added and stirred evenly, and the pH value of the solution was adjusted to 7.1 with 0.1 mol / L sodium hydroxide solution, and the stirring was continued for 2 hours. After stirring, the temperature was lowered to 23°C, filtered, washed with deionized water for 3 times, dried at 80°C, ground, and passed through a 400-mesh sieve to obtain modified montmorillonite.
[0046] The mass ratio of the montmorillonite, deionized water and hexadecyltrimethylammonium chloride is 1:28:0.4.
[0047] Example 4
[0048] Prepare modified expanded vermiculite, the preparation method of the modified expanded vermiculite is:
[0049] The expanded vermiculite and KH550 solution were mixed uniformly at a mass ratio of 1:0.06 and stirred at 55°C for 1 hour. After stirring, the mixture was cooled to room temperature and allowed to stand for 10 hours. The mixture was filtered, washed twice with deionized water, dried at 100°C, ground, and passed through a 500-mesh sieve to obtain modified expanded vermiculite.
[0050] The mass fraction of the KH550 solution is 20% of KH550 ethanol solution.
[0051] Example 5
[0052] Prepare modified expanded vermiculite, the preparation method of the modified expanded vermiculite is:
[0053] The expanded vermiculite and KH550 solution were mixed in a mass ratio of 1:0.05 and stirred at 58°C for 1 hour. After stirring, they were cooled to room temperature and allowed to stand for 8 hours. The mixture was filtered, washed with deionized water for 3 times, dried at 102°C, ground, and passed through a 500-mesh sieve to obtain modified expanded vermiculite.
[0054] The mass fraction of the KH550 solution is 20% of KH550 ethanol solution.
[0055] Example 6
[0056] Prepare modified expanded vermiculite, the preparation method of the modified expanded vermiculite is:
[0057] The expanded vermiculite and KH550 solution were mixed in a mass ratio of 1:0.07 and stirred at 60°C for 1.5 hours. After stirring, the mixture was cooled to room temperature and allowed to stand for 9 hours. The mixture was filtered, washed with deionized water for 3 times, dried at 105°C, ground, and passed through a 500-mesh sieve to obtain modified expanded vermiculite.
[0058] The mass fraction of the KH550 solution is 20% of KH550 ethanol solution.
[0059] Example 7
[0060] A corrosion-resistant PE cable, the cable comprising a PVC outer layer 1, a PE inner layer 3 and a wire core 4;
[0061] The PE inner layer 3 is coated on the outer peripheral side of the core 4, and the PVC outer layer 1 is coated on the outer peripheral side of the PE inner layer 3. A gap 2 is provided between the PVC outer layer 1 and the PE inner layer 3, and the PVC outer layer 1 and the PE inner layer 3 are separable. The gap 2 can effectively provide a space for thermal expansion and contraction of the corrosion-resistant PE cable when in use. Secondly, the gap 2 is conducive to the heat dissipation of the core 4.
[0062] The PE inner layer 3 and the PVC outer layer 1 are both formed by mixing and extruding the raw materials of the PE inner layer 3 and the raw materials of the PVC outer layer 1;
[0063] The raw material of the PVC outer layer 1 is SG-5 type PVC resin;
[0064] The raw materials of the PE inner layer 3 specifically include the following raw materials in parts by weight:
[0065]
[0066] A method for preparing a corrosion-resistant PE cable, the method specifically comprising the following steps:
[0067] S1, drying the ethylene-sodium methacrylate copolymer under vacuum at 55° C. for 22 h to obtain the dried ethylene-sodium methacrylate copolymer for later use;
[0068] S2, polyethylene, modified montmorillonite, modified expanded vermiculite, ethylene acrylic acid, ethylene-octene copolymer, glass fiber and dried ethylene-sodium methacrylate copolymer are mixed evenly and placed in a twin-screw extruder at a controlled speed of 350r / min and a temperature of 190°C for extrusion granulation to obtain PE inner layer pellets, the obtained PE inner layer pellets are extruded and molded, coated on the outer peripheral side of the wire core, cooled and solidified to obtain a semi-finished cable, PVC resin is extruded and molded, coated on the outer peripheral side of the semi-finished cable, cooled and solidified to obtain a corrosion-resistant PE cable finished product;
[0069] The extrusion molding conditions are: the feeding section temperature is 175°C, the compression section temperature is 200°C, the plasticizing section temperature is 220°C, the homogenizing section temperature is 200°C, the mold temperature is 200°C, and the cooling water temperature is 15°C.
[0070] Example 8
[0071] A corrosion-resistant PE cable, the cable comprising a PVC outer layer 1, a PE inner layer 3 and a wire core 4;
[0072] The PE inner layer 3 is coated on the outer peripheral side of the core 4, and the PVC outer layer 1 is coated on the outer peripheral side of the PE inner layer 3. A gap 2 is provided between the PVC outer layer 1 and the PE inner layer 3, and the PVC outer layer 1 and the PE inner layer 3 are separable. The gap 2 can effectively provide a space for thermal expansion and contraction of the corrosion-resistant PE cable when in use. Secondly, the gap 2 is conducive to the heat dissipation of the core 4.
[0073] The PE inner layer 3 and the PVC outer layer 1 are both formed by mixing and extruding the raw materials of the PE inner layer 3 and the raw materials of the PVC outer layer 1;
[0074] The raw material of the PVC outer layer 1 is SG-5 type PVC resin;
[0075] The raw materials of the PE inner layer 3 specifically include the following raw materials in parts by weight:
[0076]
[0077] A method for preparing a corrosion-resistant PE cable, the method specifically comprising the following steps:
[0078] S1, drying the ethylene-sodium methacrylate copolymer under vacuum at 58° C. for 23 h to obtain the dried ethylene-sodium methacrylate copolymer for later use;
[0079] S2, polyethylene, modified montmorillonite, modified expanded vermiculite, ethylene acrylic acid, ethylene-octene copolymer, glass fiber and dried ethylene-sodium methacrylate copolymer are mixed evenly and placed in a twin-screw extruder at a controlled speed of 325r / min and a temperature of 200°C for extrusion granulation to obtain PE inner layer pellets, the obtained PE inner layer pellets are extruded and molded, coated on the outer peripheral side of the wire core, cooled and solidified to obtain a semi-finished cable, PVC resin is extruded and molded, coated on the outer peripheral side of the semi-finished cable, cooled and solidified to obtain a corrosion-resistant PE cable finished product;
[0080] The extrusion molding conditions are: the feeding section temperature is 170°C, the compression section temperature is 210°C, the plasticizing section temperature is 215°C, the homogenizing section temperature is 205°C, the mold temperature is 190°C, and the cooling water temperature is 18°C.
[0081] Example 9
[0082] A corrosion-resistant PE cable, the cable comprising a PVC outer layer 1, a PE inner layer 3 and a wire core 4;
[0083] The PE inner layer 3 is coated on the outer peripheral side of the core 4, and the PVC outer layer 1 is coated on the outer peripheral side of the PE inner layer 3. A gap 2 is provided between the PVC outer layer 1 and the PE inner layer 3, and the PVC outer layer 1 and the PE inner layer 3 are separable. The gap 2 can effectively provide a space for thermal expansion and contraction of the corrosion-resistant PE cable when in use. Secondly, the gap 2 is conducive to the heat dissipation of the core 4.
[0084] The PE inner layer 3 and the PVC outer layer 1 are both formed by mixing and extruding the raw materials of the PE inner layer 3 and the raw materials of the PVC outer layer 1;
[0085] The raw material of the PVC outer layer 1 is SG-5 type PVC resin;
[0086] The raw materials of the PE inner layer 3 specifically include the following raw materials in parts by weight:
[0087]
[0088] A method for preparing a corrosion-resistant PE cable, the method specifically comprising the following steps:
[0089] S1, drying the ethylene-sodium methacrylate copolymer under vacuum at 60° C. for 24 h to obtain the dried ethylene-sodium methacrylate copolymer for later use;
[0090] S2, polyethylene, modified montmorillonite, modified expanded vermiculite, ethylene acrylic acid, ethylene-octene copolymer, glass fiber and dried ethylene-sodium methacrylate copolymer are mixed evenly and placed in a twin-screw extruder to control the speed at 300r / min and the temperature at 180°C for extrusion granulation to obtain PE inner layer pellets, the obtained PE inner layer pellets are extruded and molded, coated on the outer peripheral side of the wire core, cooled and solidified to obtain a semi-finished cable, PVC resin is extruded and molded, coated on the outer peripheral side of the semi-finished cable, cooled and solidified to obtain a corrosion-resistant PE cable finished product;
[0091] The extrusion molding conditions are: the feeding section temperature is 180°C, the compression section temperature is 205°C, the plasticizing section temperature is 210°C, the homogenizing section temperature is 210°C, the mold temperature is 195°C, and the cooling water temperature is 20°C.
[0092] Comparative Example 1
[0093] Compared with Example 7, the difference is that the modified montmorillonite prepared in Example 1 is not added in Comparative Example 1, and the other operating steps and parameters remain unchanged.
[0094] Comparative Example 2
[0095] Compared with Example 7, the difference is that the modified expanded vermiculite prepared in Example 5 is not added in Comparative Example 2, and the other operating steps and parameters remain unchanged.
[0096] Comparative Example 3
[0097] Compared with Example 7, the difference is that ethylene acrylic acid is not added in Comparative Example 3, and the other operating steps and parameters remain unchanged.
[0098] Test Example 1
[0099] Corrosion resistance test: The pellets obtained in step S2 of Examples 7-9 and Comparative Examples 1-3 were extruded under the conditions described in Example 7 to obtain test samples, and the test samples were pressed into 3 mm thick slices as test samples for acid and alkali treatment. Specifically, the acid treatment was to completely immerse the test sample in a 10wt% hydrochloric acid solution at a temperature of 60°C for 48 hours; the alkali treatment was to completely immerse the test sample in a 10wt% potassium hydroxide solution at a temperature of 60°C for 48 hours. After immersion, the sample was washed with deionized water and dried, and the same staff observed the degree of corrosion and cracking on the surface of the test sample; the results are shown in Table 1.
[0100] Table 1
[0101]
[0102] It can be seen from Table 1 that the PE inner layer granules prepared in the present invention have excellent corrosion resistance. When applied to the preparation of cables, the PE inner layer granules can effectively hinder the diffusion of foreign bodies in the finished cable products and increase the corrosion resistance of the finished cable products.
[0103] Comparative Example 4
[0104] Compared with Example 7, the difference is that no ethylene-octene copolymer is added in Comparative Example 4, and the other operating steps and parameters remain unchanged.
[0105] Comparative Example 5
[0106] Compared with Example 7, the difference is that no glass fiber is added in Comparative Example 5, and the other operating steps and parameters remain unchanged.
[0107] Comparative Example 6
[0108] Compared with Example 7, the difference is that in Comparative Example 6, no ethylene-sodium methacrylate copolymer is added, and the other operating steps and parameters remain unchanged.
[0109] Test Example 2
[0110] Toughness test: The pellets obtained in step S2 of Examples 7-9 and Comparative Examples 4-6 were extruded under the conditions described in Example 7 to prepare test samples, and the test samples were subjected to a flexural modulus test according to standard ASTM D 790. The smaller the flexural modulus, the weaker the rigidity of the material, the softer the material, and the better the toughness. The results are shown in Table 2.
[0111] Table 2
[0112] Flexural modulus (MPa) Example 7 365 Example 8 370 Example 9 370 Comparative Example 4 455 Comparative Example 5 430 Comparative Example 6 440
[0113] It can be seen from Table 2 that the PE inner layer pellets prepared in the present invention have excellent toughness.
[0114] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0115] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A corrosion-resistant PE cable, characterized in that: The cable comprises a PVC outer layer, a PE inner layer and a wire core; The PE inner layer is coated on the outer peripheral side of the wire core, and the PVC outer layer is coated on the outer peripheral side of the PE inner layer, and a gap is provided between the PVC outer layer and the PE inner layer; The PE inner layer and the PVC outer layer are both formed by mixing and extruding the PE inner layer raw material and the PVC outer layer raw material; The PVC outer layer raw material includes PVC resin; The PE inner layer raw materials specifically include the following raw materials in parts by weight: The preparation method of the modified montmorillonite comprises: controlling the temperature and stirring the montmorillonite and deionized water uniformly, adjusting the pH value of the solution after the stirring is completed, continuing the stirring, adding hexadecyltrimethylammonium chloride after the stirring is completed, stirring uniformly and adjusting the pH value of the solution, stirring again, cooling after the stirring is completed, suction filtering, washing, controlling the temperature and drying, grinding, and sieving to obtain the modified montmorillonite; The mass ratio of the montmorillonite, deionized water and hexadecyltrimethylammonium chloride is 1:25-28:0.4-0.5; The preparation method of the modified expanded vermiculite comprises the following steps: uniformly mixing the expanded vermiculite and the KH550 solution and stirring under controlled temperature, cooling and standing after stirring, suction filtering, washing, temperature-controlled drying, grinding, and sieving to obtain the modified expanded vermiculite.
2. The corrosion-resistant PE cable according to claim 1, characterized in that: The polyethylene is HDPE; The mass ratio of the expanded vermiculite to the KH550 solution is 1:0.05-0.
07.
3. A method for preparing a corrosion-resistant PE cable according to any one of claims 1 to 2, characterized in that: The preparation method specifically comprises the following steps: S1, drying the ethylene-sodium methacrylate copolymer under vacuum at controlled temperature to obtain the dried ethylene-sodium methacrylate copolymer for standby use; S2. Evenly mix polyethylene, modified montmorillonite, modified expanded vermiculite, ethylene acrylic acid, ethylene-octene copolymer, glass fiber and dried ethylene-sodium methacrylate copolymer and place them in a twin-screw extruder for speed and temperature controlled extrusion granulation to obtain PE inner layer pellets, extrude the obtained PE inner layer pellets into shapes, coat them on the outer circumference of the wire core, cool and solidify to obtain a semi-finished cable, extrude PVC resin into shapes, coat them on the outer circumference of the semi-finished cable, cool and solidify to obtain a corrosion-resistant PE cable finished product.
4. The method for preparing the corrosion-resistant PE cable according to claim 3, characterized in that: The temperature of the temperature-controlled vacuum drying in step S1 is 55-60° C. and the time is 22-24 hours.
5. The method for preparing the corrosion-resistant PE cable according to claim 3, characterized in that: The speed and temperature control in step S2 are 300-350 r / min and 180-200°C.
6. The method for preparing the corrosion-resistant PE cable according to claim 3, characterized in that: The extrusion molding conditions in step S2 are: the feeding section temperature is 170-180°C, the compression section temperature is 200-210°C, the plasticizing section temperature is 210-220°C, the homogenizing section temperature is 200-210°C, the mold temperature is 190-200°C, and the cooling water temperature is 15-20°C.
Citation Information
Patent Citations
Corrosion-resistant high-flame-retarding thermoplastic low-smoke halogen-free cable material and preparation method thereof
CN105733081A
Super-soft cold-resistant high-flame-retardant thermoplastic low-smoke halogen-free cable material and preparation method thereof
CN110791007A